2019
DOI: 10.1051/ocl/2019047
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of natural dietarytransfatty acids towards inflammation, obesity and type 2 diabetes: defining the n-7transfatty acid family

Abstract: Natural trans fatty acids are trans fatty acids that naturally occur in ruminant-derived foods: milk (derived from cow, ewe, goat), dairy products (yoghurt, cheese) and ruminant meat (beef, lamb). Because natural trans fatty acids are part of the trans fatty acid family, they have been compared for decades to their industrial counterparts on a cardiovascular outcome’s basis. At current dietary intakes, it is now well recognized that natural trans fatty acids are neutral towards cardiovascular health. Still, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Natural trans fatty acids (TFA) typically result from bacterial activity during rumen biohydrogenation of edible LA and ALA and are therefore found in ruminant-derived foods (milk and meat). Guillocheau et al recently reviewed the body of scientific knowledge on natural TFAs such as trans-palmitoleic (trans-C16:1 n-7) and trans-vaccenic (trans-C18:1 n-7) acids and highlighted that they have similar biochemical characteristics (i.e., n-7 double bond) and physiological effects [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural trans fatty acids (TFA) typically result from bacterial activity during rumen biohydrogenation of edible LA and ALA and are therefore found in ruminant-derived foods (milk and meat). Guillocheau et al recently reviewed the body of scientific knowledge on natural TFAs such as trans-palmitoleic (trans-C16:1 n-7) and trans-vaccenic (trans-C18:1 n-7) acids and highlighted that they have similar biochemical characteristics (i.e., n-7 double bond) and physiological effects [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our data also showed that some trans FA such as C18:1 t-11, C18:2 c-9, t-11, and C18:3 n-3 increase in sheep cheeses when sheep are supplemented with vegetable UFA. In humans, these natural trans FA have been related to positive effects on inflammation, obesity, and type 2 diabetes (49). More specifically, clinical trials demonstrated that naturally conjugated linoleic acid (CLA; C18:2 c-9, t-11) and C18:3 n-3-enriched cheeses are able to ameliorate the plasma lipid profile, and to reduce endocannabinoid biosynthesis (50), to reduce plasma inflammatory markers, such as IL-6, IL-8, and TNF-a (51).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies show that the risks of cardiovascular diseases with dietary trans fatty acids are attributable to industrial trans fatty acid (Oteng and Kersten, 2020). In contrast, no increase in cardiovascular risk has been observed with the consumption of naturally occurring trans fatty acids at the current consumption levels (Guillocheau et al, 2019). Studies on cells, rodents and humans suggest physiological benefits on inflammation, type 2 diabetes and obesity (Guillocheau et al, 2019), without knowing whether these naturally occurring trans fatty acids act directly or through their metabolites (Guillocheau et al, 2019).…”
Section: Health Effectsmentioning
confidence: 99%
“…In contrast, no increase in cardiovascular risk has been observed with the consumption of naturally occurring trans fatty acids at the current consumption levels (Guillocheau et al, 2019). Studies on cells, rodents and humans suggest physiological benefits on inflammation, type 2 diabetes and obesity (Guillocheau et al, 2019), without knowing whether these naturally occurring trans fatty acids act directly or through their metabolites (Guillocheau et al, 2019). Guillocheau et al recently published a comprehensive review on natural trans fatty acids (Guillocheau et al, 2019).…”
Section: Health Effectsmentioning
confidence: 99%